Roles of Motorcycle Type and Protective Clothing in Motorcycle Crash Injuries - Erdogan, Mehmet Ozgür; Sogut, Ozgur; Colak, Sahin; Ayhan, Harun; Afacan, Mustafa Ahmet; Satilmis, Dilay (Emergency Medicine International, 2013)
Background. The aims of this study were to identify subgroups of motorcyclists with a higher accident risk and evaluate the efficiency of protective clothing for preventing injuries. Methods. A 1-year prospective study of motorcycle crashes was conducted beginning in June 2012. Participants were patients involved in motorcycle crashes and admitted to our emergency department. Results. A total of 226 patients were included in the study. In total, 174 patients were involved in crashes with light motorcycles. Patients involved in a motorcycle accident without a helmet had a higher incidence of head and maxillofacial trauma. Motorcycle jackets were not protective for systemic injuries (P>0.05) or upper extremity fractures (P>0.05). Motorcycle pants (P>0.05) and motorcycle shoes (P>0.05) were not protective against leg and foot fractures. However, motorcycle protective clothes were protective against soft-tissue injuries (P=0.001). Conclusion. Riders of heavy motorcycles rode more safely than riders of light motorcycles. Light motorcycle riders were the most vulnerable and comprised the largest percentage of motorcyclists. Helmets may be effective for preventing head and facial injuries. Other protective clothes were not effective against fractures or systemic injuries.